Growth Factor Comparison in Cortical Demineralized Bone Matrix that Demineralized Using Chloric and Acetic Acid - Edward, Mouli; Mahyudin, Ferdiansyah; Basuki, Mohammad Hardian; Suroto, Heri; Perwira, Ferdiansyah Danang ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2023)
Background: Demineralized bone matrix (DBM) is an alternative biomaterial for which specific acid and immersion time are needed to optimize growth factor preservation. The optimal demineralization protocol for preserving growth factors in DBM remains unclear. This study investigated DBM extraction methods using different acids and immersion times to maintain optimal growth factor preservation.Methods: This in vitro experimental laboratory study used a randomized controlled post-test-only group design. We characterized the Insulin-like growth factor-1 (IGF-1), Bone morphogenetic protein-2 (BMP-2), and Transforming growth factor-β (TGF-β) content of 1 gram of New Zealand White Rabbit cortical bone immersed in 0.6 M hydrochloric acid and 0.5 M acetic acid for 3, 6, and 9 days. We then analyzed the differences in growth factor levels in each acid and performed statistical analysis.Results: IGF-1 levels were higher in DBM demineralized with acetic acid than with hydrochloric acid. BMP-2 and TGF-β levels were higher in DBM demineralized using hydrochloric acid. The concentration of growth factors decreased over time in DBM demineralized using acetic acid. The highest growth factor level was obtained after 6 days of immersion in hydrochloric acid.Conclusion: DBM demineralized with acetic acid yielded higher average IGF-1 levels compared to hydrochloric acid. However, BMP-2 and TGF-β levels were higher with hydrochloric acid. Growth factor levels in hydrochloric acid peaked at 6 days and then decreased. These results suggest that avoiding over-demineralization is important for maintaining growth factor levels. Further research is needed to optimize DBM processing.